Home security alarm system / Mohammad Zahiruddin Azhar, Muhamad Fahmi Mohamad and Mohd Radzin Mohd Razali - Azhar, Mohammad Zahiruddin; Mohamad, Muhamad Fahmi; Mohd Razali, Mohd Radzin (2013)
Home Security Alarm System is technologies to reduce the rate of house robbery for those who are forget to switch the alarm system on. Besides that, it is to increase safety at the house. . This project consists of 7812 IC. IC 7812 is the voltage regulator .It changes the main current to a fix current. For this circuit we are use a direct current that is 240V. When it flows through the voltage regulator it would change to 12V current. For another input, we decided to combine the motion detector device in our circuit. As you can see, there is a switch at the left corner at the figure. The switch functions as the motion detector. We change the component because there is no motion detector component in the software. When the switch is on, the output will be on. If the LDR is on and the switch is on, the LED and the buzzer will be on. If the switch is on and the LDR is off, the output also on.